Astin Bulletin: the journal of the IAA (Cambridge University Press)
ASTIN Bulletin publishes papers that are relevant to any branch of actuarial science and insurance mathematics. Its papers are quantitative and scientific in nature, and draw on theory and methods developed in any branch of the mathematical sciences including actuarial mathematics, statistics, probability, financial mathematics and econometrics.
Keywords: Economics